Exploring the Industrial Metaverse: Empowering Meta-Operators with Industry 5.0 Principles and XR Technologies - Kareem, Ali Noori; Chyad, M.A.; Salman Al-Gburib, Zahraa Dawood; Ibrahim, Husam Hamid; Sharaf, Hussien Kadhim (Society of Visual Informatics, 2024)
The term